THE EFFECT OF IMPLEMENTING OCCUPATIONAL SAFETY AND HEALTH ON THE WORK PRODUCTIVITY EMPLOYEES OF PT. PLN (PERSERO) ULP SENGKANG WAJO DISTRICT - Safira Meliana, Nurul; Yusuf Mappeasse, Muhammad; Firdaus, Firdaus (Journal of Electrical Engineering and Informatics, 2024)
The aim of this study was to determine the impact of the application of Occupational Safety and Health (K3) partially and simultaneously on the labor productivity of employees of PT PLN (Persero) ULP Sengkang Wajo Regency. For this study, a sample of 31 respondents was used using the saturated sampling method, in which all members of the population are used as samples. The analysis method used is descriptive statistics, inferential statistics and the determination of hypotheses using the t-test and the f-test using SPSS 22: (1) The application of occupational safety (X1) in the work environment of PT PLN ( Persero) ULP Sengkang Wajo Regency is in the good category overall, (2) The application of occupational health (X2) in the work environment of PT PLN (Persero) ULP Sengkang Wajo Regency is in the very good category overall, and (3) Occupational safety and health together affect the work productivity of PT PLN (Persero) ULP Sengkang Wajo Regency employees.